1999
DOI: 10.1063/1.478679
|View full text |Cite
|
Sign up to set email alerts
|

Electronic-structure calculations by first-principles density-based embedding of explicitly correlated systems

Abstract: A first-principles embedding theory that combines the salient features of density functional theory ͑DFT͒ and traditional quantum chemical methods is presented. The method involves constructing a DFT-based embedding potential and then using it as a one-electron operator within a very accurate ab initio calculation. We demonstrate how DFT calculations can be systematically improved via this procedure. The scheme is tested using two closed shell systems, a toy model Li 2 Mg 2 , and the experimentally well charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
234
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(235 citation statements)
references
References 166 publications
(74 reference statements)
1
234
0
Order By: Relevance
“…14 (For other approaches see Refs. [15][16][17][18][19][20] Our approach describes nanostructures as quantum systems embedded within a frequency-dependent dielectric medium; the systems are propagated simultaneously, coupled through an overall time-dependent potential. The method was demonstrated on a one-dimensional jellium system.…”
mentioning
confidence: 99%
“…14 (For other approaches see Refs. [15][16][17][18][19][20] Our approach describes nanostructures as quantum systems embedded within a frequency-dependent dielectric medium; the systems are propagated simultaneously, coupled through an overall time-dependent potential. The method was demonstrated on a one-dimensional jellium system.…”
mentioning
confidence: 99%
“…This new molecule object is then used to initialize and run an adfsinglepointjob, for which a higher integration accuracy and a larger basis set are used (lines [19][20][21][22]. The new results object is then used to initialize and run an adfnmrjob (lines [24][25][26]. Finally, the get_all_shieldings method of the NMR job's results object is used to extract the calculated shieldings, which can then be printed (lines [28][29][30][31].…”
Section: A Simple Example: Calculation Of Nmr Shieldingsmentioning
confidence: 99%
“…[25][26][27][28] It can be shown that using such an embedding potentials is formally exact (i.e., it is exact if the exact exchangecorrelation and kinetic-energy functionals are used and the limit of an exact WFT description is reached). 65,66 In ref.…”
Section: Wft-in-dft Embeddingmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23][24][25] Another notable implementation [26,27] resides in the CP2K code. [28] CASTEP [29] also has an implementation of FDE [30] which was employed in simulations involving two subsystems, one of which was treated at the correlated wavefunction level. [31][32][33] In addition, Turbomole [34] has its own implementation by the Della Sala group.…”
mentioning
confidence: 99%